Different levels of associations between medical co-morbidities and preterm birth outcomes among racial/ethnic women enrolled in Medicaid 2014-2015: retrospective analysis - Hyewon Lee; Ilya Okunev; Eric Tranby; Michael Monopoli (BMC, 2020)
Abstract Background The causes of preterm birth are multi-dimensional, including delayed and inadequate prenatal services as well as other medical and socioeconomic factors. This study aimed to examine the different levels of association between preterm birth and major medical co-morbidities among various racial/ethnic women enrolled in Medicaid. Methods This is a retrospective analysis of 457,200 women aged between 15 and 44 with a single live birth from the IBM® MarketScan® Multi-State Medicaid Database from 2014 to 2015. Preterm birth, defined by delivery before 37 completed weeks of gestation, was the primary dependent variable. All births were dichotomously categorized as either preterm or full-term birth using the International Classification of Diseases, Ninth Revision, Clinical Modification codes. Independent variables included race/ethnicity, categorized as non-Hispanic white, non-Hispanic black, Hispanic, or other. Medical co-morbidities included smoking, drug dependence, alcohol dependence, diabetes, and hypertension. Total healthy prenatal visit count and high-risk prenatal visit encounters identified during 30 weeks prior to the delivery date were included in the analysis. Results A significantly higher preterm birth rate was found in black women after controlled for medical co-morbidities, age, prenatal visit count, and high-risk pregnancy. Different levels of association between preterm birth outcome and major medical co-morbidities were examined among various racial/ethnic women enrolled in Medicaid. Drug dependence was associated with higher odds of preterm birth in black (OR = 2.56, 95% CI [1.92-3.41]) and white women (OR = 2.12, 95% CI [1.91-2.34]), when controlled for other variables. In Hispanic women, diabetes (OR=1.44, 95% CI [1.27, 1.64]) and hypertension (OR=1.98, 95% CI [1.74, 2.26]) were associated with higher odds of preterm birth. White women diagnosed with drug dependence had a 14.0% predicted probability of preterm birth, whereas black women diagnosed with drug dependence had a predicted probability of preterm birth of 21.5%. Conclusions The associations of medical co-morbidities and preterm births varied across racial and ethnic groups of women enrolled in Medicaid. This report calls for future research on racial/ethnic disparity in preterm birth to apply integrative and qualitative approaches to understand the disparity from a contextual perspective, especially for vulnerable pregnant women like Medicaid enrollees.